PEMANFAATAN MEDIA COMPUTER ASSISTED INSTRUCTIONAL (CAI) MODEL DRILLS PADA MATERI AJAR TRAVELLING VIOLATION PERMAINAN BOLA BASKET - WIDYA FATHIR, LUCY (Jurnal Pendidikan Olahraga dan Kesehatan, 2013)
Abstract Physical education is a process of systematic interaction between the student with the school environment through physical development effectively and efficiently towards the formation of a whole human being. Simple in the sense of teacher is one who facilitates control of the science of learning to the learners. In the field of education, the holder of the key power in the development of children’s creativity is the teacher. Learning media is one of components of the learning that has animportant in teaching and learning activities. The media as a means of communication in order to further streamline the process of teaching and learning. With the learning media, expected the quality of education will be progressively increased with the use of computer-basedmedia and one of them was CAI (Computer Assisted Instructional). This type of research is quasi experiment with quantitive descriptive approach to research design, one group pretest-posttest desidn. The population in this research is students of the eight graders in Junior High School 1 Magetan. Sampling by using cluster random sampling: sampling is not the individual but the group. The results of this research are as follows: 1) The benefits of media computer assisted instructional (CAI) model drills to the study of game rules travelling violation helped was. Evident from the results of the calculation of average difference test to sample a showed that the value of thitung > ttabel (14,639 > 2,045), then it can be concluded that there is a significant influence of media utilization of CAI. The benefits of the media is evident from the increase in calculation results with results of 66,17%. Keywords: Media Computer Assisted Instructional (CAI), model drills,  travelling violation, and basketball.